EVOLVING GENDER ROLES IN IGBO COMMUNITIES: A HISTORICAL PERSPECTIVE - Esther Chiamaka Okezie (Adisam Publisher, 2026)
Gender roles within the human societies are not fixed or permanent, and are influenced by the historical, cultural and socio-economic changes throughout history and depending on the power relations of the societies and the changing expectations of the society at different historical periods. This paper studies how gender roles in the Igbo communities have been changing historically, that is, changes over the years since the pre-colonial, colonial, and present times. The Igbo society used to be traditionally defined as a system of gender complement where men and women held different but mutually dependent roles in the economic, political, and socio-cultural arenas. The women were actively engaged in agriculture, local trade and governance of the community, through institutions like the umuada and the men-controlled Yams, long distance trade and official political systems. The paper presents the claim that such roles did not necessarily mean inequality but were designed in such a way that could provide social balance and community survival. Nevertheless, western patriarchal systems brought by colonialism changed the existing gender relations in the region by restricting the role of women in the official government, as well as redefining male and female gender roles. During the post-colonial and modern times, the gender roles have been further altered by modernization, education and globalization and thus more women are involved in education, politics and economic activities. The changes notwithstanding, some aspects of traditional gender norms and inequalities remain, which forms a complicated continuity and change interplay. Based on a historical and qualitative methodology, which relies on both primary and secondary sources, the research indicates the flexibility and strength of the gender systems in the Igbo community. It finds that to foster gender equity and formulate culturally pertinent policies across modern communities, the historical development of gender roles should be properly understood.